Optimal Design of Fuel-cell, Wind and Micro-hydro Hybrid System using Genetic Algorithm - Soedibyo Soedibyo; Heri Suryoatmojo; Imam Robandi; Mochamad Ashari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
The target of stand-alone hybrid power generation system was to supply the load demand with high reliability and economically as possible. An intelligent optimization technique using Genetic Algorithm is required to design the system.This study utilized Genetic Algorithm method to determine the optimal capacities of hydrogen, wind turbines and micro-hydro unit according to the minimum cost objective functions.The minimum cost valutes to these two factors. In this study, the cost objective function included the annual capital cost, annual operation maintenance cost, annual replacement cost and annual customer damage cost. The proposed method will be used to optimize the hybrid power generation system located in Leuwijawa village in Central Java of Indonesia. Simulation results showed that the optimum configuration can be achieved using 19.85 ton of hydrogen tanks, 21x100 kW wind turbines and 610 kW of micro-hydro unit respectively